Three‐dimensional structures of avian beta‐microseminoproteins: insight from the chicken egg‐specific beta‐microseminoprotein 3 paralog. Issue 6 (24th May 2021) - Coste, Franck; Moreau, Thierry; Labas, Valérie; Chessé, Magali; Bregeon, Mégane; Meudal, Hervé; Loth, Karine; Castaing, Bertrand; Guyot, Nicolas; Réhault‐Godbert, Sophie
Abstract : Beta‐microseminoproteins (MSMBs) are small disulfide‐rich proteins that are conserved among vertebrates. These proteins exhibit diverse biological activities and were mainly reported to play a role in male fertility, immunity, and embryogenesis. In this work, we focused on the chicken MSMB3 protein that was previously depicted as an egg antibacterial protein. We report that MSMB3 protein is exclusively expressed in the reproductive tissues of laying hens (in contrast to chicken MSMB1 and MSMB2 paralogs), to be incorporated in the egg white during the process of egg formation. We also showed that chicken MSMB3 possesses highly conserved orthologs in bird species, including Neognathae and Palaeognathae. Chicken MSMB3 was purified from egg white using heparin affinity chromatography and was analyzed by top‐down and bottom‐up proteomics. Several proteoforms could be characterized, and a homodimer was further evidenced by NMR spectroscopy. The X‐ray structure of chicken MSMB3 was solved for the first time, revealing that this protein adopts a novel dimeric arrangement. The highly cationic MSMB3 protein exhibits a distinct electrostatic distribution compared with chicken MSMB1 and MSMB2 structural models, and with published mammalian MSMB structures. The specific incorporation of MSMB3 paralog in the egg, and its phylogenetic conservation in birds together with its peculiar homodimer arrangement and physicochemical properties, suggests that the MSMB3 protein has evolved to play a critical role during the embryonic development of avian species. These new data are likely to stimulate research to elucidate the structure/function relationships of MSMB paralogs and orthologs in the animal kingdom. Abstract : Beta‐microseminoproteins (MSMBs) are small proteins conserved among vertebrates. The chicken genome contains three MSMB paralogs, which exhibit distinct tissue expression profiles, with chicken beta‐MSMB 3 (MSMB3) protein being egg‐specific. Collectively, results from protein sequence analysis, mass spectrometry analysis, and 3D structure data highlight that chicken MSMB3 possesses specific features that may be related to its presumed role in avian reproduction. ​